Dengue-free community as an approach for understanding the value and challenges of inter-agencies partnerships in an intervention program - Othman, Hidayatulfathi; Nordin, Saiful Azlan; Rashid, Norazimah Abdul; Hisham Abas, Mohamed Badrul; Hod, Rozita; Sahani, Mazrura (International Journal Of Community Medicine And Public Health, 2017)
Background: One of the key requirements for accomplishing a mutual goal is the formation of partnerships. ‘Partnership’ is an ill-defined concept, subject to multiple interpretations and frequently used interchangeably with alliance, coalition, network and collaboration among other terms. World Health Organisation had emphasized dengue prevention and control as a top priority, thus an inter agencies strategy and intervention study was launched to document the effectiveness of a local-level inter agencies approach and partnerships. Methods: The Free-Dengue Community approach, which involved stakeholder partnerships between parties such as the Ministry of Health, Ministry of Science, Technology, Local Municipalities, Health District Offices and National University of Malaysia, was developed as an inter-agencies plan for dengue prevention, of which the core objective was to design and implement activities for communication and social mobilization. In the control area, routine dengue control activities continued without additional input. Entomological indices were compared within and between the areas before and after the 12 week intervention period. Results: The approach consolidated the inter-agencies partnerships whereby the dengue cases in the localities had dropped and via this study, the module of Dengue-Free Community was mapped and documented. The result also highlighted the contributions made by each of the partner in bringing down the dengue cases in the selected localities. Furthermore, the number of ovitrap index also decreasing proving that the approach is effective. The community kit and home-kit provided to the community also helped in reducing the number of Aedes eggs in the intervention program. Conclusions: The partnership using the Dengue-Free Community approach achieved its aim of increasing the level of cooperation between the authorities to support social mobilization, and results shed light on how to tackle the challenges of inter-agency partnerships and the required approach for a better understanding of the levels at which individuals operate within such partnerships.